Solving Triangles - Part 9

Geometry Level 4

In A B C \triangle ABC , the opposite sides of A \angle A , B \angle B , and C \angle C have lengths a a , b b , and c c respectively, such that b c = 1 bc=1 and b + 2 c cos A = 0 b+2c \cos A=0 .

Find the perimeter of A B C \triangle ABC when B \angle B is the maximum . The answer can be expressed as p + q p+\sqrt q , where p p and q q are positive integers with q q being square-free. Submit p + q p+q .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Given that:

b + 2 c cos A = 0 By sine rule: sin B b = sin C c ( sin B b ) b + 2 ( sin C c ) c cos A = 0 sin B + 2 sin C cos A = 0 Note that sin B = sin ( π A C ) = sin ( A + C ) sin ( A + C ) + 2 sin C cos A = 0 sin A cos C + sin C cos A + 2 sin C cos A = 0 sin A cos C = 3 sin C cos A tan A = 3 tan C \begin{aligned} b + 2c \cos A & = 0 & \small \color{#3D99F6} \text{By sine rule: }\frac {\sin B}b = \frac {\sin C}c \\ {\color{#3D99F6}\left(\frac {\sin B}b\right)}b + 2{\color{#3D99F6}\left(\frac {\sin C}c\right)}c \cos A & = 0 \\ {\color{#3D99F6}\sin B} + 2\sin C \cos A & = 0 & \small \color{#3D99F6} \text{Note that }\sin B = \sin (\pi - A-C) = \sin (A+C) \\ {\color{#3D99F6}\sin (A+C)} + 2\sin C \cos A & = 0 \\ {\color{#3D99F6}\sin A \cos C + \sin C \cos A} + 2\sin C \cos A & = 0 \\ \sin A \cos C & = -3 \sin C \cos A \\ \implies \tan A & = - 3\tan C \end{aligned}

For A B C \triangle ABC ,

tan A + tan B + tan C = tan A tan B tan C Since tan A = 3 tan C tan B 2 tan C = 3 tan B tan 2 C tan B = 2 tan C 1 + 3 tan 2 C Divide up and down by tan C = 2 1 tan C + 3 tan C By AM-GM inequality: 2 2 3 Equality occurs when tan C = 1 3 = 1 3 \begin{aligned} \tan A + \tan B + \tan C & = \tan A \tan B \tan C & \small \color{#3D99F6} \text{Since }\tan A = - 3\tan C \\ \tan B - 2\tan C & = - 3\tan B \tan^2 C \\ \implies \tan B & = \color{#3D99F6} \frac {2\tan C}{1+3\tan^2 C} & \small \color{#3D99F6} \text{Divide up and down by }\tan C \\ & = \color{#3D99F6} \frac 2{\color{#D61F06} \frac 1{\tan C} +3\tan C} & \small \color{#D61F06} \text{By AM-GM inequality: } \\ & \le \frac 2{\color{#D61F06} 2\sqrt 3} & \small \color{#D61F06} \text{Equality occurs when }\tan C = \frac 1{\sqrt 3} \\ & = \frac 1{\sqrt 3} \end{aligned}

B \angle B is the maximum, when tan B \tan B is the maximum, max ( B ) = π 6 \implies \max (B) = \frac \pi 6 , when C = π 6 C = \frac \pi 6 , and A = 2 π 3 A = \frac {2\pi}3 . Since B = C B=C , by sine rule b = c b=c . And b c = b 2 = 1 b = c = 1 bc = b^2 = 1\implies b = c =1 and a = 2 cos π 6 = 3 a = 2 \cos \frac \pi 6 = \sqrt 3 . Therefore a + b + c = 3 + 2 a+b+c = \sqrt 3 + 2 p + q = 2 + 3 = 5 \implies p + q = 2 + 3 = \boxed 5 .


Reference:

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...